Expression of Hemolysin Is Regulated Under the Collective Actions of HapR, Fur, and HlyU in Vibrio cholerae El Tor Serogroup O1 - Gao, He; Xu, Jialiang; Lu, Xin; Li, Jie; Lou, Jing; Zhao, Hongqun; Diao, Baowei; Shi, Qiannan; Zhang, Yiquan; Kan, Biao (Frontiers in Microbiology, 2018)
The biotype El Tor of serogroup O1 and most of the non-O1/non-O139 strains of V. cholerae can produce an extracellular pore-forming toxin known as cholera hemolysin (HlyA). Expression of HlyA has been previously reported to be regulated by the quorum sensing (QS) and the regulatory proteins HlyU and Fur, but lacks the direct evidence for their binding to the promoter of hlyA. In the present work, we showed that the QS regulator HapR, along with Fur and HlyU, regulate the transcription of hlyA in V. cholerae El Tor biotype. At the late mid-logarithmic growth phase, HapR binds to the three promoters of fur, hlyU, and hlyA to repress their transcription. At the early mid-logarithmic growth phase, Fur binds to the promoters of hlyU and hlyA to repress their transcription; meanwhile, HlyU binds to the promoter of hlyA to activate its transcription, but it manifests direct inhibition of its own gene. The highest transcriptional level of hlyA occurs at an OD600 value of around 0.6-0.7, which may be due to the subtle regulation of HapR, Fur, and HlyU. The complex regulation of HapR, Fur, and HlyU on hlyA would be beneficial to the invasion and pathogenesis of V. cholerae during the different infection stages.